2017
DOI: 10.1590/0103-8478cr20160563
|View full text |Cite
|
Sign up to set email alerts
|

Leptospirosis in native mixed-breed sheep slaughtered in a semiarid region of Brazil

Abstract: Leptospirosis in native mixed-breed sheep slaughtered in a semiarid region of Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Statistically, there was no agreement between the techniques used for the detection of positive animals. Other authors found similar results in comparing serological and molecular techniques (Director et al 2014b;Costa et al 2017), thus emphasizing the need for the association of direct and indirect diagnostic methods for the reliable detection of positive animals.…”
Section: Discussionsupporting
confidence: 57%
“…Statistically, there was no agreement between the techniques used for the detection of positive animals. Other authors found similar results in comparing serological and molecular techniques (Director et al 2014b;Costa et al 2017), thus emphasizing the need for the association of direct and indirect diagnostic methods for the reliable detection of positive animals.…”
Section: Discussionsupporting
confidence: 57%
“…This study found high occurrences in Icterohaemorrhagiae and Autumnalis, with 25.21% occurrences in the former and 31.09% occurrences in the latter, which is a recurrent fact in studies related to animals in the Northeast (Costa et al, 2017;Moraes et al, 2019). This is an important fact, as it brings worries to human and animal health, once leptospirosis can also occur in occupational form, and these serogroups are important to the disease cycle in humans, especially to those in contact with the animals and their fluids, such as agricultors, slaughterhouse workers and veterinarians (Dorjee et al, 2008;Adler & De La Peña Moctezuma, 2010), and it was observed the presence of the disease in both biomes, despite their differences in soil and climate, suggesting a relation between the region studied and the occurrence of these serogroups.…”
Section: Discussionsupporting
confidence: 50%
“…Studies have reported the predominance of low titers of anti- Leptospira antibodies associated with infection in sheep flocks or samples from a slaughterhouse [15, 16, 17]. However, the microscopic agglutination test (MAT) used for serological diagnosis is not considered an adequate method to identify carriers at the individual level, since infected animals may have low or undetectable titers, necessitating the use of direct diagnostic methods for detection of carriers [18].…”
Section: Introductionmentioning
confidence: 99%